Strategi Komunikasi Ptpn Radio Melalui Konten Media Sosial Tiktok - Hastin, Tifani Yolfah; Mahar Rizqi, Fikriana (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
This study aims to analyze how PTPN Radio Solo implements communication strategies through the social media platform TikTok to reach a wider audience, particularly the younger generation. The phenomenon underlying this research is the shift in media consumption patterns, where many radio listeners have transitioned to digital platforms like TikTok for entertainment and information. In this study, the Communication Strategy theory is used to understand how communication planning can be effectively applied, while New Media Theory by Pierre Lévy explains how new media like TikTok enables more interactive communication. The research employs a qualitative descriptive method, collecting data through interviews with content creators, video editors, and PTPN Radio Solo’s audience. The findings indicate that the communication strategy implemented through TikTok, utilizing features such as For You Page (FYP), duet, stitch, and live streaming, successfully increased audience engagement and reintroduced PTPN Radio Solo to new listeners. In conclusion, the use of TikTok as part of a digital communication strategy has proven effective in enhancing interaction and strengthening PTPN Radio Solo’s position in the digital era, demonstrating how traditional broadcasting media can adapt to digital trends to remain relevant. Keywords: PTPN Radio, TikTok, Strategy